Introduction to the bilateral relations between Indonesia and the Czech Republic - Pasaribu, Kondios Meidarlin; Simanjuntak, Hotmaida; Siahaan, Monalisa Marta; Sirait, Gohima; br Tinambunan, Elizabeth (Journal Of Human And Education (JAHE), 2024)
Bilateral relations between Indonesia and the Czech Republic have been established since 1950, with a strong historical background, including President Soekarno's visit to Czechoslovakia. This cooperation covers the fields of trade, investment, education and tourism. Czechia is Indonesia's main trading partner in Central Europe, with a focus on the renewable energy sector and strategic industry. In addition, a scholarship program for Czech students in Indonesia helps strengthen cultural ties. Bilateral meetings and business forums continue to be held to explore the potential for further cooperation. Indonesia views the Czech Republic as a strategic partner in Central Europe, with a focus on increasing trade and investment value. Bilateral meetings and business forums are also frequently held to strengthen these ties, creating new opportunities for both countries in various sectors.